Exploring the Impact of Service Quality on Gold Investment Decisions: A Theory of Planned Behavior Approach - Isya Ilya, Adventa; Arif Nurohman, Yulfan (Indonesian Journal of Islamic Economics and Business, 2025)
This study aims to analyze the impact of attitude, subjective norm, and perceived behavioral control on Islamic gold investment decisions using the Theory of Planned Behavior (TPB) approach, and to examine the moderating role of service quality among Bank Muamalat Solo Raya customers. Employing an explanatory quantitative method with survey design, data from 150 respondents investing in Solusi Emas Hijrah (SOLEH) products were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results reveal that only subjective norm significantly influences investment intention (β = 0.316, p = 0.041), while attitude (β = 0.103, p = 0.347) and perceived behavioral control (β = 0.128, p = 0.474) show no significant effect. Service quality demonstrates a significant direct effect on investment behavior (β = 0.288, p = 0.002) but fails to function as a moderator in all tested hypotheses. Investment intention strongly predicts investment behavior (β = 0.606, p = 0.000), confirming the core TPB proposition. The model explains 46.2% variance in intention and 63.5% in behavior. Findings indicate a dual-path mechanism in Islamic gold investment behavior formation: the first path operates through subjective norm → intention → behavior, and the second through service quality's direct influence on behavior. The study contributes theoretically by demonstrating the need for TPB contextualization in collectivist cultures where social influence dominates over individual psychological factors. Practically, results suggest that Islamic banks should emphasize community-based marketing approaches and maintain high service quality standards to effectively drive actual investment behavior.